Study on Hydrodynamic Mechanism of Feature Points in Tidal Reach of Lower Minjiang River - LIAO Tingting; CHEN Mingxing (Renmin Zhujiang)
To accurately determine the roughness of bed surface of the tidal reach,and explore the response relationship between the flow velocity of downstream feature points and the tidal level,the flow velocity of feature points and that of the Guantou,according to different vegetation on different elevation above the water,and different sand size in different beds under water,this paper determines the roughness of underlying surface,and accurately simulates and analyzes the hydrodynamic characteristics of tidal reach of the Minjiang River.The results show that:The periodic changes of tidal level fit well with the verification results of measured values,and both the tidal level and the flow velocity show periodic changes.There is a response lag between the change trend of tidal level and flow velocity.The farther the feature point of the tidal reach away from the estuary,the longer the lag time of flow velocity,and the linear equation of the trend of both is y=0.0384x.